If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + -7)(8x + 7) = 0 Reorder the terms: (-7 + 8x)(8x + 7) = 0 Reorder the terms: (-7 + 8x)(7 + 8x) = 0 Multiply (-7 + 8x) * (7 + 8x) (-7(7 + 8x) + 8x * (7 + 8x)) = 0 ((7 * -7 + 8x * -7) + 8x * (7 + 8x)) = 0 ((-49 + -56x) + 8x * (7 + 8x)) = 0 (-49 + -56x + (7 * 8x + 8x * 8x)) = 0 (-49 + -56x + (56x + 64x2)) = 0 Combine like terms: -56x + 56x = 0 (-49 + 0 + 64x2) = 0 (-49 + 64x2) = 0 Solving -49 + 64x2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + 64x2 = 0 + 49 Combine like terms: -49 + 49 = 0 0 + 64x2 = 0 + 49 64x2 = 0 + 49 Combine like terms: 0 + 49 = 49 64x2 = 49 Divide each side by '64'. x2 = 0.765625 Simplifying x2 = 0.765625 Take the square root of each side: x = {-0.875, 0.875}
| 5(10-c)=125 | | -27.84=5.6x+8 | | -2(v-8)-4v=-7(v-1) | | 5(u-2)=9u+2-2(-6u-3) | | 2.5(z+4)=3.75 | | 296+29+x-24= | | y^2-2yx-3x^2=0 | | (c+3)/2=5 | | -9(x-5)=x+22(2) | | 5.1+1.4n=2.16 | | 5v+4=-11 | | H(x)=x^2-3x-15 | | -63=7(x-9) | | 93+3x+18= | | -71-9m=82 | | 4x-4-24=0 | | (x-5y)(5x+y)=0 | | 4e-16+5e=29 | | 8x+6+7x+14= | | 6.3+0.5h=16.3 | | 1.6n+3.8n=54 | | 7.1x-2.8=24.18 | | 56=-8x | | -5y=-12 | | m+4=-3m | | (3x^2-5x-5)+(9x^2+2x+1)= | | 105x+112= | | X^2+0.02x-0.07=0 | | 6.3+0.5=16.3 | | 6(2-r)=15 | | 130+11x-2= | | .6p-.8=.6666p |